New plant breeding technologies for food security - Zaidi, Syed Shan-e-Ali; Vanderschuren, Hervé; Qaim, Matin; Mahfouz, Magdy M.; Kohli, Ajay; Mansoor, Shahid; Tester, Mark (Science (American Association for the Advancement of Science), 2019)
Improved crops can contribute to a world without hunger, if properly managed A world without hunger is possible but only if food production is sustainably increased and distributed and extreme poverty is eliminated. Globally, most of the poor and undernourished people live in rural areas of developing countries, where they depend on agriculture as a source of food, income, and employment. International data show a clear association between low agricultural productivity and high rates of undernourishment ( 1 ). Global studies have also shown that rapid reduction of extreme poverty is only possible when the incomes of smallholder farmers are increased ( 2 ). Therefore, sustained improvement in agricultural productivity is central to socioeconomic development. Here, we argue that with careful deployment and scientifically informed regulation, new plant breeding technologies (NPBTs) such as genome editing will be able to contribute substantially to global food security.